Synopsis: Seasonality and household diets in Ethiopia - Hirvonen, Kalle; Taffesse, Alemayehu Seyoum; Worku, Ibrahim (Ethiopian Development Research Institute, 2015)
The paper revisits seasonality by assessing how the quantity and quality of diets vary across agricultural seasons in rural and urban Ethiopia. Using unique nationally representative household level data for each month over one calendar year, we document seasonal fluctuations in household diets in terms of both the quantity of calories and the number of different food groups consumed. Households in both rural and urban areas consume less calories in the lean season, but interestingly, due to changes in the composition of diets, the diet diversity score increases towards the end of the lean season.